2009
DOI: 10.1007/s00431-009-1064-3
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of congenital heart defects in Croatia

Abstract: Abstract:1 2The aim of our study was to investigate the incidence of congenital defects in children born in Croatia during a 3 period of 5 years, its association with extracardiac malformations, its treatment and outcome. Medical 4 information about the patients was obtained from 14 paediatric cardiology centres that cover the whole country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
31
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 30 publications
3
31
0
3
Order By: Relevance
“…Karande et al, Miller et al and Dilber and Malcic found incidence of extracardiac anomalies 17.5%, 13.5% and 14.5% respectively which was lower than our study. [10][11][12] Down syndrome is the most common identified syndrome in our study. The prevalence of congenital heart disease in down syndrome was similar to the findings from other studies, which have been between 44% and 62%.…”
Section: Discussionmentioning
confidence: 65%
“…Karande et al, Miller et al and Dilber and Malcic found incidence of extracardiac anomalies 17.5%, 13.5% and 14.5% respectively which was lower than our study. [10][11][12] Down syndrome is the most common identified syndrome in our study. The prevalence of congenital heart disease in down syndrome was similar to the findings from other studies, which have been between 44% and 62%.…”
Section: Discussionmentioning
confidence: 65%
“…The frequency of chromosomal abnormalities reported in subsets of patients from other studies ranged from 2.6 to 12.5% (usually around 9%) 7,8,[18][19][20][21][22][23]25,26,29,30 . Our study detected the highest rate (14.6%) and was the only one to perform karyotype analysis in all patients and to specifically assess this approach.…”
Section: Discussionmentioning
confidence: 99%
“…It demonstrates the importance of physical examination, by an expert such as a clinical geneticist, on the suspicion of occurrence of malformations in other organs or systems. In our literature review, we did not find reports classifying patients into syndromic or not by dysmorphological physical examination 7,[8][9][10][18][19][20][21][22][23][24][25][26][27][28][29][30] . Kramer et al 19 pointed that the recognition of minor malformations may serve as indicator of general problems in morphogenesis and may constitute valuable clue in the diagnosis of specific patterns of malformations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations